Construction of a mathematical model of the influence of various environmental factors on the plant biomass on the contaminated soil by toxic elements (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2020)
The article has been devoted the development of a program for constructing a mathematical model based on the processing of experimental data for modeling plant biomass on soil contaminated with toxic elements.In general, the problem under consideration is relevant in areas where forecasting based on analysis of data for previous points in time is required in order to take into account the relationship between the values of a certain set of factors and the behavior of an object or in the process which represented by a time seriesThe proposed software product for solving the problem of analyzing multidimensional time series is universal and can be applied in various fields - in ecology, medicine, chemistry, pharmacology, economics, and others. Models constructed using this method are superior to regression models in their predictive properties, due to the fact that, thanks to the application of heuristic principles of self-organization, automatic selection of informative input variables and selection of the structure of the optimal regression model.  The construction of mathematical models from experimental data is carried out automatically. In the process of modeling, the main task is the identity of the form   dependence and the choice of factors that have a significant impact on the dependent variable. Moreover, the structure of the model, in contrast to the regression analysis, is not fixed in advance, but is selected from a variety of options according to the absolute error criterion.Using the self-organization program, we estimated the dependence of plant biomass (Miscanthus), which has a high biological absorption of heavy metals from contaminated soil from the precipitation, air temperature, potential evaporation of moisture in the soil and photosynthetic active radiation during the year, taking into account the approximation confidence value. Was obtained the mathematical models of biomass ‘plant depending from the environmental factors. The analysis showed that the predictors that have the greatest effect on plant biomass growing on soil contaminated with heavy metals are evaporation of soil moisture, photosynthetic active radiation and precipitation. The data obtained are relevant for predicting the processes of cleaning contaminated soil using plants.